Augmenting reality: fusing consumers' experiences and interactions with immersive technologies in physical retail settings. (20th January 2020) - Bonetti, Francesca; Pantano, Eleonora; Warnaby, Gary; Quinn, Lee
Drawing upon previous research into immersive environments and technology-enhanced stores, this exploratory study elucidates the concept of the 'augmented store' – a physical store modified to accommodate augmented reality (AR) technology. In doing so, it extends previous research conducted in experimental laboratory settings to an empirical real-world scenario. Qualitative data gathered from interviews with, and observation of, consumers using AR technology in-store are analysed to provide naturalistic understandings of interactions with, and perceptions of, a physical store enhanced with AR technology. Findings suggest that consumers appreciate the ability to experience an enhanced, more immersive store environment arising from the AR experience. They perceive interaction with the augmented store to be 'realistic' and articulated hedonic motivations as drivers for interaction in this shopping environment. The augmented store appears to stimulate brand engagement, increasing consumers' desire to shop at the retailer, providing managerial opportunities to reinforce brand positioning.